DNA barcoding of deep-sea shrimp Sicyonia parajaponica Crosnier, 2003 (Crustacea: Decapoda: Sicyoniidae) from southwest coast of India - Chakraborty, Rekha Devi; Gayathri, A.p.; Sreelakshmy, S.; Aghana, M.; Kuberan, G. (Zootaxa, 2021)
The present work reports detailed taxonomic information on deep-sea shrimp Sicyonia parajaponica from southwest Indian waters. The samples were caught in bottom trawls conducted between the depths of 200 and 230 m from Sakthikulangara fishing harbour off Kollam, Kerala along the Arabian Sea during November 2019. DNA barcoding and a phylogenetic analysis was used to explore the relationship of the genus Sicyonia based on mitochondrial cytochrome c oxidase subunit 1 (COI: MN816389, MN816390) with the present specimen and sequences retrieved from NCBI GenBank. There is no difference in the intraspecies genetic distance (0%) while interspecies genetic distance (19.0–28.1%) revealed divergence between the species (COI) of the genus Sicyonia.